The Hammadids moving from the AL Qal'a to Bejaia: a study of causes and Results - Hemmoum, Khaled (Journal of Human Sciences, 2022)
Under the leadership of their Prince Hammad bin Belkin, the Hammadids seized the Qal'a of Bani Hammad and made it the capital of their state within the year 398 ah/1007 ad, and they stayed there for about half a century, then they moved to Bejaia during the era of their fifth Prince Al-Nasir bin Alnas in 461 ah/1069 ad, and they took it as the new capital of their state and called it Nasiriyah.The reasons for their move to Bejaia have multiplied, and historians have mentioned two important reasons, avoiding the crawling of the Arabs of Bani Hilal and economic prosperity, as for the results of this transition, the most important of them is the availability of safety, scientific development, and the prosperity of maritime trade thanks to the huge Bejaia port.